GP commissioning in England - Charlton, Rodger (Clin Med (Lond), 2013)
The NHS, yet again, is in transition with an emphasis on groups of general practitioners (GPs) (clinical commissioning groups) making decisions on which specialist services should be chosen for patients requiring referral from primary care. It is an area of new terminology with a new language and further change for all working in the NHS and the all-important interface between primary and secondary care, and its impact on teamwork. There are many drivers including choice, efficiency, franchising of services, coordination and leadership in an enormous organisation, but not least reducing costs and keeping to a budget. There are many logistical issues and ethical anxieties, and only time will inform patients, practitioners, stakeholders and politicians as to its success.